Heat transfer characteristics of single row of jets issuing from screw-thread nozzles impinging on a concave surface. (December 2021) - Xu, Liang; Yun, Xue; Xi, Lei; Gao, Jianmin; Yang, Tao; Li, Yunlong
Abstract: Based on the combination of experiment and numerical analysis, the heat transfer characteristics of single row of swirling jets impinging on a concave semi-cylindrical surface are studied. The effects of nozzle shape, jet pitch ( c/D = 4, 6, 8), swirl number ( S = 0.15, 0.32, 0.56) and impinging distance ( H/D = 2, 3, 4, 5) are investigated. For the single row of impinging jets, the entrainment vortices enhance the flushing on the target, and the backflow vortices increase gradually along the vertical direction with the increase of c/D . The average Nusselt number ( Nu ave ) of the swirling impinging jet (SIJ) is higher than that of the conventional round impinging jet (CIJ) under the same conditions. With the increase of the c/D, the Nu ave(s) in the circumferential direction and the Nu ave(x) in the axial direction decrease. Compared with c/D = 8, the Nu ave(x) of the SIJ is 13.4% higher than that of c/D = 4 under the same test conditions. In addition, S has a weak effect on the Nu distribution of the SIJ. With the increase of the H/D, the Nu ave(s) and the Nu ave(x) both decrease. The Nu ave(s) and Nu ave(x) for H/D = 5 are both about 5% higher than those for H/D = 2.